Analisis Semantik dalam Teks Prajñāpāramitā Hṛdaya Sūtra: Kajian Linguistik dan Hermeneutik Buddhis Mahayana - Ingrid Sia Susana Elis (Jurnal Budi Pekerti Agama Buddha, 2024)
This article examines the semantic meaning in the Prajñāpāramitā Hṛdaya Sūtra (Heart Sūtra), one of the important sūtras in the Mahāyāna Buddhist tradition. Using a qualitative approach, this article integrates semantic and hermeneutical theories to understand the structure of meaning, symbolism, and interpretation contained in the text. The analysis focuses on key words such as śūnyatā (emptiness), negation structures, and closing mantras as symbolic forms towards enlightenment. The study employs close reading methodology combined with semantic field theory, polysemy analysis, and apophatic language frameworks. The results show that a semantic approach deepens the understanding of Buddha's teachings and their relevance in spiritual practice. This article also highlights how meaning in the text is not only linguistic, but also existential and contemplative, demonstrating that religious language in Mahāyāna functions as metalanguage pointing beyond conceptual understanding.